The LTC training dilemma: finding the right training company. - Enyeart S (Long-Term Living: For the Continuing Care Professional, 2008)
Training is one of the most important benefits you can give your staff -- and residents. You don't have to go it alone. However, when choosing a training company, make sure you know what to look for.